Students' views and qualification policy development: perspectives on failed vocationally related policies (UCL Press, 2013)
Despite the fact that students are often articulate about qualifications policy matters, their perspectives are rarely listened to. This is because governments shape qualifications policy according to pre-set beliefs and are unwilling to countenance dissonant or outsider views. Using the Diploma qualification and inclusion of vocational qualifications as General Certificate of Secondary Education and A level equivalents for league tables as examples, this commentary complements this edition's main articles through exploring why these policies failed, as well as why myriad voices went unheeded.